Effect of aluminum content on structure, transport and mechanical properties of Sn-Zn eutectic lead free solder alloy rapidly solidified from melt. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The greatest advantage of Sn-Zn eutectic is its low melting point (198 oC) which is close to the melting point. of Sn-Pb eutectic solder (183 oC), as well as its low price per mass unit compared with Sn-Ag and Sn-Ag-Cu solders. In this paper, the effect of 0.0, 1.0, 2.0, 3.0, 4.0, and 5.0 wt. % Al as ternary additions on melting temperature, microstructure, microhardness and mechanical properties of the Sn-9Zn lead-free solders were investigated. It is shown that the alloying additions of Al at 4 wt. % to the Sn-Zn binary system lead to lower of the melting point to 195.72 ?C. From x-ray diffraction analysis, an aluminium phase, designated ?-Al is detected for 4 and 5 wt. % Al compositions. The formation of an aluminium phase causes a pronounced increase in the electrical resistivity and microhardness. The ternary Sn-9Zn-2 wt.%Al exhibits micro hardness superior to Sn-9Zn binary alloy. The better Vickers hardness and melting points of the ternary alloy is attributed to solid solution effect, grain size refinement and precipitation of Al and Zn in the Sn matrix. The Sn-9%Zn-4%Al alloy is a lead-free solder designed for possible drop-in replacement of Pb-Sn solders.